Rapid identification of human SNAP‐25 transcript variants by a miniaturized capillary electrophoresis system. Issue 2 (14th September 2013) - Németh, Nóra; Kerékgyártó, Márta; Sasvári‐Székely, Mária; Rónai, Zsolt; Guttman, András; Foret, Franta; Kutter, Jörg P.
<x xml:space="preserve">Abstract</x> The 25 kDa synaptosomal‐associated protein (SNAP‐25) is a crucial component of the soluble N‐ethylmaleimide‐sensitive factor attachment protein receptor complex and plays an important role in neurotransmission in the central nervous system. SNAP‐25 has two different splice variants, SNAP‐25a and SNAP‐25b, differing in nine amino acids that results in a slight functional alteration of the generated soluble N‐ethylmaleimide‐sensitive factor attachment protein receptor complex. Two independent techniques, a PCR–miniaturized CE method and a real‐time PCR based approach were elaborated for the specific and quantitative detection of the two SNAP‐25 transcription variants. DNA‐constructs coding for the two isoforms were used for optimization. Excellent specificity was observed with the use of our previously described highly sensitive miniaturized CE system in combination with quantitative PCR. The ratio of the two isoforms were reliably detected in a range of at least four orders of magnitude with a linear regression of R2 = 0.987. Expression of the two isoforms was determined in human samples, where SNAP‐25 was detected even in non‐neural tissues, although at approximately a 100‐fold lower level compared to the central nervous system. The relative amount of the SNAP‐25b isoform was higher in the brain, whereas expression of SNAP‐25a variant proved to be slightly higher in extra‐neural cell types. The genomics approach in conjunction with the miniaturized CE system introduced in this paper is readily applicable for rapid alternative splice variant analysis.